Improving the Laplace transform integration method. (3rd November 2015) - Lynch, Peter; Clancy, Colm
Abstract : We consider the Laplace transform filtering integration scheme applied to the shallow‐water equations, and demonstrate how it can be formulated as a finite‐difference scheme in the time domain. In addition, we investigate a more accurate treatment of the nonlinear terms. The advantages of the resulting algorithms are demonstrated by means of numerical integrations.